Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/jmse8090651
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sources Supporting Macro-Invertebrate Communities in Restored Mangrove Forests from Hau Loc, Thanh Hoa, Vietnam

Abstract: Mangrove forests are important in providing habitats for complex communities of terrestrial and marine fauna. Moreover, they are recognized as highly productive ecosystems in providing nutrients to mangrove food webs or exporting them to nearby coastal waters. In the present study, stable isotopes of carbon and nitrogen were applied to examine the changes in the diets of benthic invertebrate communities following mangrove restoration. The isotope signature of invertebrate tissues varied among the forest ages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The mangrove forest biomass is significantly higher than seagrass, which provides a vital source of OC for coastal waters. The POM in coastal water and estuaries in sampling areas was higher than the previous research in Thanh Hoa, Red River Delta [4,22]. This pattern may be related to the geomorphological settings of Tien Yen Bay, causing the mangrove materials to not be accessible and exported to open water, leds to low values of δ 13 C in POM samples [21].…”
Section: Roles Of Mangrove Forest In Organic Carbon Accumulationmentioning
confidence: 70%
See 1 more Smart Citation
“…The mangrove forest biomass is significantly higher than seagrass, which provides a vital source of OC for coastal waters. The POM in coastal water and estuaries in sampling areas was higher than the previous research in Thanh Hoa, Red River Delta [4,22]. This pattern may be related to the geomorphological settings of Tien Yen Bay, causing the mangrove materials to not be accessible and exported to open water, leds to low values of δ 13 C in POM samples [21].…”
Section: Roles Of Mangrove Forest In Organic Carbon Accumulationmentioning
confidence: 70%
“…[1][2]. They also provide critical ecological functions and services such as nursing habitat, feeding zone, breeding grounds for aquatic species, waterbirds, migratory birds, and providing high economic benefits for humans [3][4][5]. Recently, mangrove forests have been degraded globally due to human activities such as aquaculture, urbanization, industry, and agriculture [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…According to Feng et al (2017), changes in the structure of mangrove vegetation communities can affect the availability and palatability of food sources for leaf-eating crabs. Van Hieu et al (2020) discovered that crabs primarily feed on phytoplankton and benthic microalgae in mudflats, while in Sonneratia caseolaris and Kandelia candel forests, their diet consists mainly of benthic microalgae and sediment organic matter. Past studies have shown differences in the food sources of crabs in mangrove margin areas and forest interior areas (Kruitwagen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%